Factors influencing student engagement in physical education: Evidence from urban and rural secondary schools in Tanzania - Mduwile, Peter Lameck; Lufunga, Janeth; Goswami, Dulumoni (Tanjungpura Journal of Coaching Research, 2026)
Background. Learning outcomes in physical education (PE) are dependent on student engagement. Student engagement refers to the level of motivation, participation, and students’ propensity to remain active learners over time. Differences in school resources and socio-economic status between urban and rural schools may result in varied levels of student engagement towards learning PE. Objectives. To explore factors that influence student engagement in physical education among secondary school students in urban and rural schools in Tanzania. Methods. Employing a sequential mixed-methods approach, data was collected from 12 secondary schools selected from three regions in Tanzania (Dar es Salaam, Morogoro, and Dodoma). Quantitative data was collected through student engagement questionnaires. Qualitative data was collected through teacher interviews and classroom observation. The independent sample t-test and regression were used to compare and identify factors contributing to student engagement between urban and rural schools. Results. Statistically significant differences were found between urban and rural students’ engagement levels. Students from urban schools scored higher on behavioral engagement (3.8±0.6 vs 3.4±0.7; p=0.014), emotional engagement (3.6±0.5 vs 2.9±0.6; p=0.001), and cognitive engagement scores (3.7±0.5 vs 3.1±0.6; p=0.002). Teacher quality of instruction, learning resources, and parental academic support had positive contributions to student engagement, while household responsibilities and lack of sports infrastructure had negative contributions towards rural students’ engagement. Conclusion. Student engagement in PE is influenced by factors within and outside the education system which create achievement gaps between urban and rural schools. Recommendations: To close achievement gaps, programs should be developed to increase access to quality teacher training, technological resources, and sports infrastructure. Parental involvement should also be considered a mechanism to help increase equitable student engagement.